(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
Since ancient times, spices such as black pepper, cinnamon, ginger, turmeric, garlic, black cumin, clove, ocimum, saffron, and nutmeg constitute an important part of foods and beverages in India. Besides, adding aroma and flavour to the food, they are also known for multiple medicinal benefits. During the COVID-19 pandemic, an interesting pattern of disease prevalence and severity was observed especially in the countries where spices are consumed regularly. It has attracted researchers worldwide to explore the therapeutic potential of spices in COVID-19 management. Various in silico studies have reported good binding affinities of spices and derived components towards structural druggable targets of SARS-CoV2. There are several compelling pieces of evidence for the role of spices in the attenuation of inflammatory cytokine storm which is the crux in the pathogenesis of COVID-19. Therefore, this review is written to provide deep insights into the role of food spices and their underlying mechanism in targeting SARS-CoV2. Based on experimentally verified data from different in-vitro, in-vivo, in-silico, and clinical studies, the information presented will certainly help in the development of promising drug therapeutics or preventive strategies to deal with SARS-CoV2. Further studies geared towards the development of drugs based on spices and derived compounds are suggested.